Fully High‐Speed Gravure Printed, Low‐Variability, High‐Performance Organic Polymer Transistors with Sub‐5 V Operation. (18th January 2016) - Grau, Gerd; Subramanian, Vivek
Abstract : Printed transistors will be a key component in low‐cost, large area, flexible printed systems such as flexible displays, sensor networks, or radio‐frequency identification (RFID) tags. In any such applications, these printed organic thin‐film transistors (OTFTs) will have to operate at low voltages, exhibit good uniformity, and deliver relatively high performance by using scaled source and drain electrodes. In addition, devices need to be printed at high speeds to fully harness the potential of low‐cost fabrication that printed electronics promises. Gravure printing is a particularly promising technique because it combines high resolution in the sub‐10 μm regime with high printing speed on the order of 1 m s –1 . Here, for the first time, fully gravure‐printed OTFTs are demonstrated that use highly scaled source and drain electrodes with linewidth and spacing of 5 μm. All layers are printed at 1 m s –1 . An amorphous polymer semiconductor is used to achieve good uniformity. By patterning the semiconductor and scaling the dielectric, good off‐state performance and sub‐5 V operation are achieved, thus providing a promising path for the realization of functional printed systems. Abstract : Fully high‐speed printed organic thin‐film transistors are demonstrated. All layers are gravure printed at 1 m s –1 with source–drain and channel dimensions of 5 μm. Good uniformity is achieved by employing an amorphous polymer semiconductor. By patterning the semiconductor and scaling the dielectric, low‐voltage operation below 5 V is achieved. This is a promising result for the realization of low‐cost, large area, flexible printed systems.